Ambient Agent Model for Supporting Volunteers during Stress - Alw, Asmidah; Ab Aziz, Azizi; Che Pa, Noraziah; A Abubakara, Juliana; Hanis Mohd Shabli, Ahmad; MohdTaufik Wan Ismail, Wan (International Journal of Engineering and Technology, 2018)
Stress during natural disaster has been reported everywhere. Stress is a common psychological stimulus that occurs in a person caused by stressors. Natural disaster is a specific form of stressor that can carry wide area of implications within the population. It is the most common factor which contributes to high level of stress and other psychological problems of individuals. This article proposed an ambient agent model to support volunteers who experienced stress during flooding event. Set of properties and variables are identified through past literatures and series of interview to construct the model. A number of well-known relations between events and the courses of stress are summarized and it is shown that the model exhibits their patterns. Differential equations have been used in formalizing the model. Set of equations reflecting relations involved in the proposed model are presented. From the developed models, a variety of simulation experiments was conducted. The proposed model is essential and can be encapsulated within an intelligent agent or robots that can be used to support volunteers who experienced stress during flood.Â Â